O estudante de medicina no Conselho Municipal de Saúde: construindo a responsabilidade social - Morita, Ione [UNESP]; Almeida, Margareth Aparecida Santini De [UNESP] (Associação Brasileira de Educação Médica, 2008)
The formational function of the university must establish a relationship with the society to be able to respond to its needs. In this connection, medical schools have been promoting curricular reforms seeking for new teaching and learning scenarios responding as much to the principles of the Brazilian Health System as to the Curricular Guidelines, complementing each other in the sense of preparing critical professionals for the health area. The objective of this paper was to describe the extra-curricular activities performed by students in the Municipal Health Council of Botucatu in the period 2000-2005, and their perception of the role of these activities in their formation. With regard to the methodology, the students participated in MHC meetings, red the records, interviewed the members of the council, participated in encounters held for preparing health councilors and elaborated an evaluative report. The students were unanimous in appreciating this experience, which allowed them to develop reflective capacity, part of the construction of social responsibility. The experience also contributed to the articulation of teaching and social demands, the expected role of the university, promoting a change in the persons involved.

As escolas médicas vêm promovendo reformas curriculares, buscando novos cenários de ensino e aprendizagem, respondendo tanto aos princípios do Sistema Único de Saúde quanto às Diretrizes Curriculares, que se complementam no sentido de se dispor de profissionais críticos na área da saúde. Este artigo descreve as atividades de extensão desenvolvidas por alunos no Conselho Municipal de Saúde (CMS) de Botucatu (SP) no período de 2000-2005 e sua percepção sobre essas atividades em sua formação. Os estudantes freqüentaram as reuniões do CMS, leram as atas, entrevistaram os conselheiros, participaram de encontros de saúde promovidos para formar conselheiros de saúde e elaboraram um relatório de avaliação. Os alunos foram unânimes em valorizar esse contato e, por meio dessa experiência, desenvolveram a capacidade reflexiva, parte da construção da responsabilidade social. Cumpriu-se, também, a articulação entre ensino e demandas sociais, papel esperado da universidade, contribuindo para uma mudança das pessoas envolvidas.
The medical student in the Municipal Health Council: constructing social responsibility
Keywords: Student, Medical; Health Planning Councils; Social Responsibility; Estudantes de Medicina; Conselhos de Saúde; Responsabilidade Social